FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA PT. PLN WILAYAH SUMUT CABANG LUBUK PAKAM RANTING MEDAN DENAI - Simangunsong, Elisabeth (Jurnal Manajemen dan Bisnis, 2016)
Elisabeth, This study aims to identify and analyze the factors that affect customer satisfaction. Benefits of the research is to provide input to the PLN in order to deliver a quality service. The population of this study were all customers of PT. PLN (Persero) Regional Branch of North Sumatra Medan Denai Lubukpakam Branch. A sample of 125 respondents. Data collection techniques by questionnaire and documentation. Data analysis techniques by factor analysis. Results of research and discussion shows from 25 variables were observed before the rotation are 15 variables that have a correlation coefficient above 0.5 setelahrotasi to 23 variables as the dominant factor influencing customer satisfaction. Of the 23 variables are grouped into eight factors: Factor 1: Understanding customer needs, quick service, hospitality employees, Employee Attitudes, place of service is safe and sympathetic attitude. FACTOR 2: Attention sincere, timeliness of service and employee performance. FACTOR 3: The equipment used and the speed of service, FACTOR 4: Respond to complaints and handling problems, FACTOR 5: Concern officer, Presedur petition and competence of employees, FACTOR 6: Willingness employee help, Conformity implementation and Recency of equipment, FACTOR 7: Information clear and sense of security during the deal and FACTOR 8: Attention Patience officers and employees. Conclusion There are 23 variables as the dominant factor affecting customer satisfaction, namely: understanding customer needs, fast service, friendliness of employees, employee attitudes, a safe care, attitudes sympathetic, genuine concern, timeliness of service, the appearance of an employee, the equipment used , speed of service, response to complaints, troubleshoot problems, care attendant, Presedur petition and employee competencies, employee willingness to help, Conformity implementation, recency equipment, clear information, Sense of security during the deal, the attention of officers and employees Patience. While the suggestions need to improve the quality of services quickly and accurately through the training and development of employees, disseminating the manual system with computerized equipment online payment of electricity bills to provide convenience for customers and establish mutually beneficial relationship